(untitled) (JOURNAL OF ADVANCES IN AGRICULTURE, 2017)
A factorial experiment with randomized complete block design carried out in Erbil governorate, Iraq during 2015 and 2016 seasons on pear (Pyrus Communis L.) Spadona and Compote cvs. to investigate the effects of spraying trees with (0, 0.5, 1.0 and 1.5%) salicylic acid (SA) on some fruits quantity and quality characteristics. The results show that Compote fruits had the highest weight and firmness significantly compared to Spadona fruits in both seasons, whereas Spadona variety records the highest total acidity. Fruits of Compote variety records higher chlorophyll a , chlorophyll b and total carotenoids content significantly compared to Spadona variety in 2015, in the opposite of the results of 2016 in respect to chlorophyll a and chlorophyll b. Spraying trees with SA increased fruit weight and firmness compare to control treatment for both seasons, and total acidity in 2015 and total sugars in 2016, whereas the differences were not significant in 2016 and 2015 for the last two properties. In 2015 spraying 1.5% SA increased each of chlorophyll a and b content significantly compared to other concentrations, whereas significant decrease in total carotenoids content observed with increasing SA concentration, whereas the differences between SA treatments were not significant in 2016 in respect to chlorophyll a, b and total carotenoids.